Urinary catecholamine excretion in tetanus. - Thwaites, C; Yen, L; Cordon, S; Binh, N; T, N; Nga, N; White, N; Soni, N; MacDonald, I; Farrar, J (2006)
Imperfect understanding of the pathophysiology of tetanus has limited therapeutic advances. Autonomic disturbance is a major cause of mortality and is believed to be associated with catecholamine release, predominantly norepinephrine. We measured epinephrine and norepinephrine concentrations in 24-h urine collections from tetanus and critically ill patients suffering from other severe diseases. In patients with severe tetanus, mean (SD) epinephrine was 164.18 (129.37) nmol x day(-1) compared with 45.18 (37.74) nmol x day(-1) in mild-moderate disease (p = 0.008). In the severe group, mean (SD) norepinephrine was 411.64 (208.5), and 121.00 (81.81) nmol x day(-1) in moderately ill patients (p < 0.001). Compared with critically ill control patients, median epinephrine was 331.77 in tetanus patients and 89.70 nmol x day(-1) in controls (p < 0.001). Median norepinephrine concentration was 788.02 nmol x day(-1) in tetanus and 300.05 nmol x day(-1) in control patients, p = 0.006. The study finds a novel result of increased epinephrine excretion in tetanus and confirms that catecholamine excretion in tetanus exceeds that in other critically ill patients. These results should be considered in designing more effective therapeutic strategies.